Pengaruh Investasi, Indeks Pembangunan Manusia (IPM), Tenaga Kerja, Upah Minimum Terhadap PDRB Per Kapita 10 Provinsi Terendah Di Indonesia - Desrifani Erza; Idris (Universitas Negeri Padang, 2025)
This study examines the effect of various factors on the Gross Regional Domestic Product (GRDP) per capita of the 10 provinces with the lowest per capita GRDP in Indonesia over the period 2016–2024. The factors analyzed include Investment, Human Development Index (HDI), Labor Force, Minimum Wage. The research employs secondary data obtained from various sources, including the Central Bureau of Statistics (BPS) and other relevant institutions. The analytical method used is panel data regression, processed using Eviews 12 with the Random Effect Model (REM) approach. The results indicate that investment has a positive and significant effect on GRDP per capita, while the Human Development Index (HDI) has a negative and insignificant effect. The labor force variable shows a positive but insignificant effect, and the minimum wage has a positive and significant effect on the GRDP per capita of the 10 lowest-ranked provinces in Indonesia during the 2016–2024 period.